Pembelajaran Double Loop Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematis - Pratama, Oktavia Irma; Suherman, Suherman (Desimal: Jurnal Matematika, 2018)
The purpose of this study was to determine the effect of learning models Double Loop Problem Solving (DLPS) to the ability problem solvimg mathematical students. This research was a quantitative research type of quasi experiment. The sampling technique that used was random class technique. The sampel in this research was the VII B grade as a experimental class and the VII E grade as a control class. Data analysis technique of this research was normality test, homogeneity test and hypothesis test by using one-party t-test. Based on the result of t-test analysis of one party with significant level 5% with description , So the result of the research can be concluded that there was influence of learning models Double Loop Problem Solving (DLPS) to the ability problem solving of mathematically.